Big money, corruption, and black markets: A closer look at the legal and economic effects of amateurism in division I NCAA college athletics. Issue 4 (9th September 2019) - Custis, Tyler; Hoben, Meghan; Larsen, Payton
Abstract : Purpose: The purpose of this paper is to explore why the stagnant version of amateurism that is being used by the National Collegiate Athletic Association (NCAA) and its member institutions to limit student–athlete compensation is creating labor law and antitrust violations, and ultimately contributing to a black market in college athletics. Design/methodology/approach: The qualitative portion of the examination uses a review of historic and recent cases regarding labor law and antitrust violations and applies them to the college athletic industry. Furthermore, the quantitative portion creates a scaled revenue sharing calculation utilizing financial reports from university athletic departments and corresponding professional revenue-sharing agreements to discern an approximate value of a student–athlete's participation. Findings: The authors find that the current structure of the NCAA and regulatory framework perpetuate injustice for those who lack a voice in the system. Furthermore, the research shows a wage disparity of millions of dollars creating a lack of free market and black-market tensions to reach free market equilibrium. Social implications: This research creates reasoning to restructure the NCAA system to adjust for modern commercialization and profits of the industry. Originality/value: This paper highlights the legal and regulatory abuses by the NCAA, and demonstrates how the compensation gap created by these legal violations is creating a strain on free market flow ultimately leading to a black-market effect in the industry.